Creeping fat exhibits distinct Inflammation-specific adipogenic preadipocytes in Crohn’s disease - Hwang, Nahee; Kang, Dongwoo; Shin, Su-Jin; Yoon, Bo Kyung; Chun, Jaeyoung; Kim, Jae-woo; Fang, Sungsoon (Frontiers in Immunology, 2023)
Creeping fat (CrF) is an extraintestinal manifestation observed in patients with Crohn's disease (CD). It is characterized by the accumulation of mesenteric adipose tissue (MAT) that wraps around the intestinal wall. Although the role of CrF in CD is still debated, multiple studies have highlighted a correlation between CrF and inflammation, as well as fibrostenosais of the intestine, which contributes to the worsening of CD symptoms. However, the mechanism underlying the potential role of CrF in the development of Crohn's fibrosis remains an enigma. This study aimed to analyze CrF comprehensively using singlecell RNA sequencing analysis. The data was compared with transcriptomic data from adipose tissue in other disease conditions, such as ulcerative colitis, lymphedema, and obesity. Our analysis classified two lineages of preadipocyte (PAC) clusters responsible for adipogenesis and fibrosis in CrF. Committed PACs in CrF showed increased cytokine expression in response to bacterial stimuli, potentially worsening inflammation in patients with CD. We also observed an increase in fibrotic activity in PAC clusters in CrF. Co-analyzing the data from patients with lymphedema, we found that pro-fibrotic PACs featured upregulated pentraxin-3 expression, suggesting a potential target for the treatment of fibrosis in CrF. Furthermore, PACs in CrF exhibited a distinct increase in cell-to-cell communication via cytokines related to inflammation and fibrosis, such as CCL, LIGHT, PDGF, MIF, and SEMA3. Interestingly, these interactions also increased in PACs of the lymphedema, whereas the increased MIF signal of PACs was found to be a distinct characteristic of CrF. In immune cell clusters in CrF, we observed high immune activity of pro-inflammatory macrophages, antigen-presenting macrophages, B cells, and IgG + plasma cells. Finally, we have demonstrated elevated IgG + plasma cell infiltration and increased pentraxin-3 protein levels in the fibrotic regions of CrF in CD patients when compared to MAT from both UC patients and healthy individuals. These findings provide new insights into the transcriptomic features related to the inflammation of cells in CrF and suggest potential targets for attenuating fibrosis in CD.